ZAKAT ON GOLD JEWELLERY: CASE OF TERENGGANU - Ahmad, Salina; Nazri, Siti Maisarah (Jurnal ’Ulwan, 2024)
One type of zakat al-dhahab (gold) is zakat on gold jewellery which is a conditional obligation. However, not many Muslims understand its hukm as much as they understood other types of zakat like zakat fitrah. Looking at the current trend of keeping gold jewellery as an investment; it is a call for a more serious study to investigate the level of knowledge of it. This study intends to explain the Malaysian context of zakat on gold, Terengganu practice of zakatable gold jewellery and the knowledge of Diploma in Muamalat students of UiTM Terengganu branch on it. The research adapts mixed methods research (MMR), a research design that has both philosophical assumptions and multiple methods of inquiry in a single study. Underlying Islamic hukm on zakat al-dhahab is discovered through library research while particular research issue is investigated through interviews. The study finds that the obligation of zakat on gold jewellery in Malaysia derived from a long tradition of Islamic jurisprudence of different schools. Guidelines from the Malaysian authority have been given due attention in Terengganu practice to cater with contemporary development of gold investment by providing peculiar ‘urf of the state. The majority of informants have basic knowledge about zakat on gold, as expected from students undertaking Islamic Muamalat programmes. It can be asserted that, ‘urf plays a very important role in determining hukm on Islamic jurisprudence, especially in dynamic areas not provided by the nass. The level of knowledge of Diploma in Muamalat students in UiTM Terengganu branch with regard to theoretical knowledge on zakat fulfils the minimum requirement. It is suggested, however, that more detailed analyses be done on ‘urf as determining factor effecting the obligation of certain mu’amalat instruments. Future studies can address, for example, zakat on gold investment in Malaysia as a potential socially responsible investment.